(untitled) (Conferencea, 2021)
Light gray soils are widespread in the republic. Only in the Fergana region, they occupy 140,780 hectares. These soils are divided into pebble, irrigated serozem, in places calmatized, light and medium loamy, and gravelly-pebble-loamy eroded.